How Capital Intensity, Sales Growth, and Inventory Intensity Influence Tax Aggressiveness - Rahma, Ayumi; Agustinus, Erick; Finatariani, Endah (Universitas Pamulang, 2025)
Taxation constitutes a major component of government revenue, serving as a crucial instrument for financing public expenditures and supporting national development programs. On the other hand, corporations tend to view taxes as a reduction in earnings and therefore seek ways to reduce the burden, one of which is through tax aggressiveness. Although still within the boundaries of tax regulations, such practices diminish potential state revenue and remain a concern for policymakers. This research explores the influence of capital intensity, sales growth, and inventory intensity on corporate tax aggressiveness. The study focuses on firms in the food and beverage sub-sector listed on the Indonesia Stock Exchange between 2019 and 2023. The sample was determined using purposive sampling in line with predetermined criteria, while panel data regression was employed for hypothesis testing. The findings reveal that capital intensity, sales growth, and inventory intensity jointly exert a significant impact on tax aggressiveness. Moreover, partial analysis confirms that each variable individually contributes to explaining variations in tax aggressiveness. These results underscore the importance of firm-level financial policies in shaping corporate tax behavior.